Guideline for Promoting Self-Adaptation among Older Adults with Stage 1 Dementia through Process Art Activities (PCRS Model) - Katkaew, Kitnithi; Pholprasert, Apichart; Boonyananta, Soamshine (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
This academic article aimed to propose a guideline for promoting self-adaptation among older adults with stage 1 dementia through process art activities. The findings from the study revealed that both Thailand and foreign countries gave importance to encouraging perception and memory, emotion-focused therapy, and self-esteem. The use of process art activities could help train the nervous and brain system, reduce stress, practice fine motor skills, build self-worth and self-esteem increasingly. The guideline for promoting self-adaptation among older adults with stage 1 dementia through activities was based on the proposed process art or PCRS model. This is generated from the synthesis of documents and research relevant to art activities for older adults with stage 1 dementia, that has been held no longer than 10 years from reliable sources, both databases and websites for aging adults or websites providing activities for older adults. Details of PCRS model were as follow: 1) P: Process Art – experience is managed to meet things around older adults. Emphasis is placed on the 5 senses, 2) C: Collaboration – it helps older adults have interaction with friends and learn social skills through doing activities together, 3) R: Reflection – older adults’ life experiences are reflected through activities, 4) S: Self-Monitoring – older adults assess themselves by keeping a record of what happened in the past, observing, and writing suggestions to themselves that which point in the past can be improved.